Avaliação da função sócio-ambiental da Floresta Nacional de Canela (RS) como subsídio ao ecoturismo e educação ambiental - Santos, Nara Rejane Zamberlan dos (2005)
A study was carried out in Canela, RS, including the application of instruments which evaluated the characteristics of the receiving region, the tourist profile, Canela s National Forest evaluation by the tourists the area around the FLONA and the National Forest area itself, with the objectives of evaluating the social function of this Unit of Conservation and its use a subsidy to ecotourism and environmental education. The methodology was based on the evaluation of 14 instruments, applied in eight phases of data collection. The results confirmed the vocation of Canela for tourism, based on its hotel infrastructure, food and drink, as well as furniture, chocolate and handcraft industries. The high season tourists (July and December) possess higher socio economic and cultural standards of living than the low season tourists (October and February). The area around Canela s National Forest formed by the Ulisses de Abreu uptown presented a neighborhood population formed by employed heads of the family, resident in the houses wooden, with a young family nucleus, due to the numbers of children present. The tourist was considered attraction to be its good accesses and regular signaling. Canela National Forest was appointed as a protected area with touristic potential. The evaluation of the Forest landscape by the tourists, in four periods, through landscape substitutes, demonstrated distinct differences of perception formed by two groups, the first of women and male teenagers, between 15-20 years old, and the second group, formed by the other men. The analysis of the view of twenty-two sub-landscapes proved to be the same multiples with half-limited reach and perception of the landscape determined three factors in the landscape perception such as, the factor, of scenery including the water and the scenic background, the anthropic factor, constituted by human performances and the color and the vegetation factor. The Visitors Center of Canela s National Forest registered the presence of visitors who were, in the majority, students and professors, from the Rio Grande do Sul state. The Forest structure showed deficiencies in technical staff, in its infrastructure and in the Visitors Centre. The Veado Track located in the interior of the Forest presented an inferior number of attractions in relation to the initial proposal, and these were found to be lacking in signaling. In the visual quality of the elements present in the Veado Track were perceived partially defined lines, organic forms, medium texture degree a random order, with colors of little variation and few green tonalities. Based on the climatic data a load capacity for the track was proposed depending on the season of the year and the size of the groups. The analysis of the attractions of Veado Track of determined the possibility of its use in ecotourism and its application in inherent subjects of environmental education.